Lithium slag modified slag powder for inhibiting alkali aggregate reaction of concrete and preparation method thereof

CN122958083APending Publication Date: 2026-10-23LIANGSHAN SAIDI BUILDING MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611133592.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

粉煤灰和矿渣主要通过火山灰反应消耗部分氢氧化钙并降低孔溶液碱度,但在碱活性较强或长期潮湿的服役环境中,仅依靠降低体系碱度难以持续阻断钠离子、钾离子与活性二氧化硅的反应

Benefits of technology

本发明将精炼渣、高炉矿渣和锂渣按照70:21:9的质量比配合,并使高炉矿渣与锂渣按照70:30的质量比组成改性料。锂渣提供锂组分,锂离子能够优先作用于活性硅表面的反应位点,减少钠离子、钾离子与活性二氧化硅结合形成膨胀性碱硅凝胶;锂离子还能够与活性二氧化硅反应形成吸水膨胀性低的硅酸锂产物,从而抑制碱骨料反应引起的膨胀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958083A_ABST
    Figure CN122958083A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of building materials, and discloses lithium slag modified slag powder for inhibiting concrete alkali aggregate reaction and a preparation method thereof, wherein the lithium slag modified slag powder comprises refining slag, blast furnace slag and lithium slag in a mass ratio of 70:21:9; the blast furnace slag and the lithium slag form a modified material, and the mass percentages of the two in the modified material are 70% and 30% respectively; the lithium slag contains Li2O; and the mass content of SO3 in the lithium slag modified slag powder is not more than 3.0%. During preparation, the refining slag, the blast furnace slag and the lithium slag are proportioned according to the set ratio, and the lithium slag modified slag powder is obtained through mixing and synchronous grinding. According to the application, the blast furnace slag and the lithium slag are compounded, and the refining slag, the blast furnace slag and the lithium slag are synergized, so that the lithium component is introduced while the SO3 content is controlled, the generation of expansive alkali-silica gel is reduced, the concrete alkali aggregate reaction is effectively inhibited, and the resource utilization level of industrial solid waste is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and more specifically, to a lithium slag modified powder for inhibiting alkali-aggregate reaction in concrete and its preparation method. Background Technology

[0002] Alkali-aggregate reaction in concrete refers to the phenomenon where alkaline components within the concrete react with active components in the aggregate, causing expansion and damage. This mainly includes alkali-silica reaction and alkali-carbonic acid reaction. During the alkali-silica reaction, the highly alkaline pore solution formed during cement hydration dissolves the active silica in the aggregate, which then reacts with sodium and potassium ions to form alkali-silica gel with water-absorbing and expanding properties. As the alkali-silica gel continues to absorb water and expand, internal stress is generated at the aggregate-paste interface, leading to the propagation of microcracks within the concrete. In severe cases, this can result in through-cracks, reducing the strength, impermeability, and frost resistance of the concrete structure.

[0003] Existing technologies typically suppress alkali-aggregate reactions by limiting the alkali content of concrete, selecting inactive aggregates, incorporating fly ash or slag, and adding lithium salt admixtures. However, with the gradual depletion of inactive aggregate resources, it is difficult to completely avoid using aggregates containing active siliceous minerals in some regions. Fly ash and slag primarily consume some calcium hydroxide and reduce the alkalinity of the pore solution through pozzolanic reaction. However, in service environments with strong alkali reactivity or prolonged dampness, simply reducing the system's alkalinity is insufficient to sustainably block the reaction between sodium and potassium ions and active silica. While directly adding lithium salts can suppress alkali-aggregate reactions, lithium salt admixtures are expensive to purchase and may affect the bleeding, segregation, and workability of concrete.

[0004] Lithium slag, produced during lithium smelting, contains Li₂O and exhibits pozzolanic activity, making it usable as a mineral lithium source. However, using lithium slag alone presents challenges such as insufficient early hydration activity, fluctuations in chemical composition depending on the batch of raw materials, and high SO₃ content. Insufficient lithium slag dosage makes it difficult to effectively suppress alkali-aggregate reaction, while excessive dosage may affect material stability. Furthermore, the synergistic utilization of refining slag, blast furnace slag, and lithium slag lacks a formulation and grinding scheme that balances lithium content, activity, and SO₃ content. Therefore, it is necessary to provide a modified lithium slag powder for suppressing alkali-aggregate reaction in concrete and its preparation method. Summary of the Invention

[0005] In view of this, the present invention provides a lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete and its preparation method, aiming to solve the above problems.

[0006] On the one hand, the present invention provides a lithium slag modified powder for inhibiting alkali-aggregate reaction in concrete, comprising: The mixture comprises refining slag, blast furnace slag, and lithium slag, wherein the mass ratio of the refining slag, blast furnace slag, and lithium slag is 70:21:9; the lithium slag contains Li2O; the blast furnace slag and lithium slag constitute a modifier, wherein the mass percentages of the blast furnace slag and lithium slag in the modifier are 70% and 30%, respectively; the refining slag, blast furnace slag, and lithium slag are mixed and ground to form the modified lithium slag powder, wherein the SO3 mass content in the modified lithium slag powder does not exceed 3.0%.

[0007] Preferably, the Li2O content in the lithium slag is 1.06% by mass, and the Li2O content in the modified material is 0.30% to 0.34% by mass.

[0008] Preferably, the lithium slag comprises the following chemical composition by mass percentage: CaO 15.45%, SiO2 44.53%, Al2O3 19.48%, MgO 0.59%, Fe2O3 1.87%, SO3 15.51%, Na2O 0.52%, K2O 0.58%, and Li2O 1.06%.

[0009] Preferably, the refining slag comprises the following chemical composition by mass percentage: CaO 43.26%, SiO2 26.18%, Al2O3 10.72%, MgO 8.54%, Fe2O3 6.31%, SO3 0.58%, Na2O 0.21%, and K2O 0.34%.

[0010] Preferably, the 28-day activity index of the modified lithium slag powder is not less than 97%; when the modified lithium slag powder replaces cement by an equal amount of 25% of the total mass of cementitious materials, the 14-day expansion rate measured by the rapid mortar bar method is less than 0.03%.

[0011] On the other hand, the present invention also provides a method for preparing lithium slag modified slag powder that inhibits alkali-aggregate reaction in concrete, comprising the following steps: Refining slag, blast furnace slag and lithium slag were obtained respectively, and the mass content of Li2O in the lithium slag and the mass content of SO3 in the refining slag, blast furnace slag and lithium slag were detected. The amount of lithium slag added is determined based on the mass content of Li2O in the lithium slag. Blast furnace slag and lithium slag are mixed at a mass ratio of 70:30 to prepare a modified material, so that the mass content of Li2O in the modified material is 0.30% to 0.34%. The refining slag and modified material are mixed at a mass ratio of 70:30. The SO3 mass content after mixing is calculated based on the SO3 mass content in the refining slag, blast furnace slag and lithium slag, so that the calculated SO3 mass content does not exceed 3.0%. The refined slag, blast furnace slag and lithium slag after batching are mixed and simultaneously ground to obtain the modified lithium slag powder.

[0012] Preferably, when determining the amount of lithium slag to be added, the mass content of Li2O in the modified material is calculated according to the following formula: C = aC1 + bC2; In the formula, C is the mass content of Li2O in the modified material, a is the mass fraction of blast furnace slag in the modified material, C1 is the mass content of Li2O in the blast furnace slag, b is the mass fraction of lithium slag in the modified material, and C2 is the mass content of Li2O in the lithium slag.

[0013] Preferably, when the mass content of Li2O in different batches of lithium slag changes, the amount of lithium slag and blast furnace slag added is adjusted so that the mass content of Li2O in the modified material is between 0.30% and 0.34%, and the sum of the mass percentages of blast furnace slag and lithium slag is 100%.

[0014] Preferably, the simultaneous grinding includes feeding the finished refining slag, blast furnace slag and lithium slag into a ball mill for grinding, so that the three raw materials are refined and uniformly mixed during the grinding process.

[0015] Preferably, after obtaining the modified lithium slag powder, the modified lithium slag powder is subjected to stability testing and activity index testing. The modified lithium slag powder with qualified boiling stability, 28-day activity index not less than 97%, and SO3 mass content not exceeding 3.0% is determined as the finished product.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention combines refining slag, blast furnace slag, and lithium slag in a mass ratio of 70:21:9, and further combines blast furnace slag and lithium slag in a mass ratio of 70:30 to form a modified material. The lithium slag provides the lithium component, allowing lithium ions to preferentially act on the reaction sites on the surface of active silicon, reducing the formation of expansive alkali-silica gels by the combination of sodium and potassium ions with active silica. Lithium ions can also react with active silica to form lithium silicate products with low water absorption and expansion, thereby inhibiting the expansion caused by the alkali-aggregate reaction.

[0017] This invention utilizes the complementary interaction between blast furnace slag and lithium slag. The blast furnace slag participates in the hydration reaction and consumes calcium hydroxide, reducing the reaction conditions for alkali-aggregate reaction. The lithium slag continuously provides lithium components, addressing the lack of a lithium-ion inhibition pathway when using blast furnace slag alone. Refined slag, blast furnace slag, and lithium slag are co-ground to form fine and uniformly distributed particles, which can act as micro-fillers and improve the pore structure of the slurry. This inhibits alkali-aggregate reaction from multiple aspects, including reducing the alkalinity of the pore solution, limiting alkali-ion reaction, and reducing water absorption and swelling conditions. Experimental results show that when the prepared lithium slag-modified slag powder replaces cement at 25% of the total mass of cementitious materials, the 14-day expansion rate of the mortar rod is 0.026%, lower than the 0.03% threshold for effective inhibition.

[0018] This invention determines the amount of lithium slag to be added based on the Li2O content in the lithium slag and calculates the SO3 content after batching. While ensuring the modified material provides lithium components, the SO3 content in the modified lithium slag powder is controlled to within 3.0%, thereby reducing the risk of sulfate expansion caused by excessive lithium slag. The finished product is controlled through stability, activity index, and SO3 content testing. The resulting modified lithium slag powder exhibits qualified boiling stability and a 28-day activity index of not less than 97%, effectively balancing alkali-aggregate reaction inhibition and gelling activity.

[0019] This invention uses refining slag, blast furnace slag, and lithium slag as main raw materials, eliminating the need for additional lithium salt admixtures. It simultaneously utilizes industrial solid waste generated during steelmaking, ironmaking, and lithium smelting. The resulting modified lithium slag powder is used as a mineral admixture to replace a portion of the cement, reducing cement usage and solid waste accumulation. C30 concrete test results show that after replacing cement with 25% of the total cementitious material mass, the 28-day compressive strength of the concrete reaches 37.5 MPa, meeting the strength requirements of C30 concrete while suppressing alkali-aggregate reaction. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a comparison chart of the average expansion rate of mortar rods in Example 1 and Comparative Example 1 of the present invention.

[0022] Figure 2 This is a comparison chart of the 14-day expansion rate of mortar bars under different lithium slag dosage conditions according to the present invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] This invention provides a lithium slag modified powder for inhibiting alkali-aggregate reaction in concrete, comprising refining slag, blast furnace slag, and lithium slag. The mass ratio of refining slag, blast furnace slag, and lithium slag is 70:21:9. Blast furnace slag and lithium slag constitute the modified material, with the mass percentages of blast furnace slag and lithium slag in the modified material being 70% and 30%, respectively, and the modified material accounting for 30% of the total mass of the lithium slag modified powder.

[0026] The refining slag used in this embodiment is the raw material obtained by pretreatment of the refining slag produced during the steelmaking refining process. The main chemical components of the refining slag are shown in Table 1.

[0027] Table 1. Main chemical components of refining slag

[0028] The ordinary refining slag powder used had a 45μm sieve residue of 1.8% and a density of 2.89 g / cm³. 3 The specific surface area is 460 m² / kg, the fluidity ratio is 103%, the 7-day activity index is 71%, the 28-day activity index is 100%, the free CaO content is 0.11%, and the boiling stability is qualified.

[0029] The blast furnace slag used in this embodiment is blast furnace slag produced during the steel production process. Blast furnace slag does not contain lithium, has a specific surface area of ​​425 m² / kg, and a 28-day activity index of 98%. Blast furnace slag contains calcium, silicon, and aluminum components, which can participate in the hydration reaction and consume some of the Ca(OH)₂ produced during cement hydration, thereby reducing the alkalinity of the pore solution and compensating for the insufficient early hydration activity when lithium slag is used alone.

[0030] The lithium slag used in this embodiment is lithium smelting waste generated during lithium salt smelting. It appears as a grayish-white powder and exhibits pozzolanic activity. The residual Li₂O in the lithium slag serves as the lithium source in the modified material. The main chemical components of the lithium slag are shown in Table 2.

[0031] Table 2 Main chemical components of lithium slag

[0032] Because lithium slag produced by different lithium smelting processes may vary in Li2O and SO3 content between batches, the chemical composition of refining slag, blast furnace slag, and lithium slag is tested separately before production. Chemical composition testing can be performed according to the methods specified in GB / T 176, density according to the methods specified in GB / T 208, specific surface area according to the methods specified in GB / T 8074, and free calcium oxide content according to the methods specified in YB / T 4328.

[0033] When blast furnace slag and lithium slag are used to form modified materials, the Li2O content in the modified materials is calculated using a mass-weighted method, as shown in the following formula: C(Li₂O)=a C1+b C2.

[0034] In the formula, C(Li2O) is the mass content of Li2O in the modified material; a is the mass fraction of blast furnace slag in the modified material; C1 is the mass content of Li2O in the blast furnace slag; b is the mass fraction of lithium slag in the modified material; and C2 is the mass content of Li2O in the lithium slag.

[0035] When the blast furnace slag contains no Li2O, the Li2O content in the lithium slag is 1.06% by mass, and the mass percentages of the blast furnace slag and lithium slag are 70% and 30% respectively, the Li2O content in the modified material is: C(Li2O)=70%×0+30%×1.06%=0.318%≈0.32%.

[0036] It should be noted that 0.32% refers to the Li2O mass content in the modified material composed of blast furnace slag and lithium slag. The modified material accounts for 30% of the total mass of the final lithium slag modified powder. Therefore, based on the aforementioned raw material data, the theoretical Li2O mass content in the final lithium slag modified powder is: 30% × 0.318% = 0.0954%.

[0037] The main chemical components of the modified material are shown in Table 3.

[0038] Table 3 Main chemical components of the modified material

[0039] Since the SO3 content in lithium slag is 15.51%, excessive addition of lithium slag may increase the risk of sulfate expansion. Therefore, when determining the amount of lithium slag to be added, the SO3 content in the final modified lithium slag powder is calculated using a weighted average method based on the SO3 test results of refining slag, blast furnace slag, and lithium slag, and is controlled to be below 3.0%.

[0040] When concrete undergoes an alkali-silica reaction, cement hydration produces Ca(OH)₂, maintaining the alkalinity of the concrete pore solution. The reactive amorphous SiO₂ in the aggregate dissolves in this alkaline environment and reacts with Na₂ in the pore solution. + and K + The reaction produces alkali-silica gel with water-absorbing and swelling properties. After absorbing free water from inside the concrete, the alkali-silica gel expands in volume, generating tensile stress at the interface between the aggregate and the paste, which in turn leads to the generation and propagation of microcracks.

[0041] Li leached from lithium slag + It can migrate to the aggregate interface and act on the reaction sites on the active silica surface, reducing Na +and K + It combines with active SiO2 to form an expandable alkali silica gel. Li + It can also react with active SiO2 to form lithium silicate products with low water absorption and swelling, forming a barrier structure on the aggregate surface and reducing the continued entry of alkaline components from the pore solution into the aggregate. Blast furnace slag participates in the pozzolanic reaction and consumes some Ca(OH)2, reducing the reaction conditions for alkali-aggregate reaction; after refining slag, blast furnace slag, and lithium slag are co-ground to form fine and uniformly distributed particles, which can fill the pores inside the slurry and reduce the free water and pore space required for the water absorption and swelling of alkali silica gel.

[0042] Example 1

[0043] This embodiment provides a lithium slag modified powder that inhibits alkali-aggregate reaction in concrete. The specific preparation process is as follows.

[0044] (1) Raw material testing

[0045] Refining slag, blast furnace slag, and lithium slag were obtained separately, and the chemical composition of each raw material was analyzed to determine the mass content of Li2O in the lithium slag and the mass content of SO3 in the refining slag, blast furnace slag, and lithium slag.

[0046] In this embodiment, the lithium slag contains 1.06% Li₂O and 15.51% SO₃ by mass; the refining slag contains 0.58% SO₃ by mass. The blast furnace slag does not contain lithium.

[0047] (2) Preparation of modified materials

[0048] Blast furnace slag and lithium slag were weighed at a mass ratio of 70:30, and the blast furnace slag and lithium slag were premixed to obtain modified material.

[0049] Taking the preparation of 3000 kg of modified material as an example, 2100 kg of blast furnace slag and 900 kg of lithium slag are weighed. According to the mass-weighted method, the mass content of Li2O in the obtained modified material is 0.318%, which is 0.32% after rounding to two decimal places.

[0050] (3) Total ingredients

[0051] The refining slag and modified material are weighed according to a mass ratio of 70:30. Taking the preparation of 10,000 kg of lithium slag modified powder as an example, 7,000 kg of refining slag and 3,000 kg of modified material are weighed. The 3,000 kg of modified material includes 2,100 kg of blast furnace slag and 900 kg of lithium slag. Therefore, the final mass ratio of refining slag, blast furnace slag, and lithium slag in the batch is 70:21:9.

[0052] The SO3 content in the final batch is calculated based on the SO3 content of the refining slag and the modified material. In this embodiment, the SO3 content of the refining slag is 0.58%, and the SO3 content of the modified material is 6.24%. The theoretical SO3 content in the final batch is 70% × 0.58% + 30% × 6.24% = 2.278%, which is approximately 2.28% and does not exceed 3.0%. Therefore, it proceeds to the grinding process.

[0053] (4) Mixing and grinding

[0054] The refined slag, blast furnace slag, and lithium slag, after being batched, are fed into a ball mill for simultaneous grinding. This process refines the particles and ensures uniform mixing of the three raw materials, resulting in modified lithium slag powder. Simultaneous mixing and grinding reduces localized enrichment of lithium slag in the finished product, ensuring a uniform distribution of lithium components within the modified lithium slag powder.

[0055] (5) Finished product inspection

[0056] The obtained modified lithium slag powder was tested for SO3 content, boiling stability, and activity index. The theoretical mass content of SO3 in the obtained modified lithium slag powder was approximately 2.28%, not exceeding 3.0%. The boiling stability test was conducted according to the method specified in GB / T 1346. The test cake showed no cracks or warping, indicating that the stability was qualified. The 28-day activity index was 97%.

[0057] Comparative Example 1

[0058] This comparative example uses ordinary refined slag powder without the addition of blast furnace slag and lithium slag. Ordinary refined slag powder is made by grinding refined slag and does not contain lithium components.

[0059] The residue of ordinary refined slag powder on a 45μm sieve is 1.8%, and its density is 2.89 g / cm³. 3 The specific surface area is 460 m² / kg, the fluidity ratio is 103%, the 7-day activity index is 71%, the 28-day activity index is 100%, the free CaO content is 0.11%, and the boiling stability is qualified.

[0060] Test Example 1: Alkali-Aggregate Reaction Inhibition Performance Test

[0061] Rapid slurry bar tests were conducted using lithium slag modified slag powder prepared in Example 1 and ordinary refined slag powder prepared in Comparative Example 1 to verify the inhibitory effect of different slag powders on alkali-aggregate reaction.

[0062] The experiment used reference cement, silica-alkali reactive aggregate, standard sand, analytical grade NaOH reagent, and tap water. The chemical properties of the reference cement are shown in Table 4, and the physical properties are shown in Table 5.

[0063] Table 4 Chemical properties of reference cement

[0064] Table 5 Physical properties of reference cement

[0065] The test was conducted according to the rapid mortar bar method specified in Appendix A of GB / T 50733. Mineral admixtures were used to replace 25% of the total mass of cementitious materials with the reference cement (440g), standard sand (990g), and a water-cement ratio of 0.47. The mortar bars were 25mm × 25mm × 280mm in size, with three parallel specimens per group.

[0066] After 24 hours of molding, the mortar rods were demolded and pre-cured in clean water for 24 hours, then transferred to a 1 mol / L NaOH solution at 80℃±2℃ for further curing. The baseline length and lengths at 3d, 7d, 10d, and 14d were measured. The average value of three parallel samples from each group was taken as the expansion rate. The expansion rate of the mortar rods was calculated using the following formula: P t =(L t -L0) / L0×100%.

[0067] In the formula, P t The expansion rate of the mortar rod after curing for t days; L t L0 is the length of the mortar bar after curing for t days; L0 is the reference length of the mortar bar.

[0068] The 14-day expansion rate was used as the criterion for determining the effectiveness of the inhibition. When the 14-day expansion rate was less than 0.03%, the mineral admixture was deemed to have an effective inhibitory effect on the alkali-aggregate reaction; when the 14-day expansion rate reached or exceeded 0.03%, the mineral admixture was deemed to have failed to effectively inhibit the alkali-aggregate reaction.

[0069] The test results of Example 1 and Comparative Example 1 are shown in Table 6.

[0070] Table 6. Expansion rate of different slag powder mortar rods

[0071] The changes in the average expansion rate of the mortar rods in Example 1 and Comparative Example 1 are as follows: Figure 1 As shown in Table 6, the average expansion rate of the mortar bars in Comparative Example 1 continued to increase with the extension of the curing period, while the increase in the average expansion rate of the mortar bars in Example 1 was significantly limited. At 14 days of curing, the average expansion rate of Comparative Example 1 was 0.117%, and the average expansion rate of Example 1 was 0.026%. Table 6 shows that the expansion rate of the mortar bars in Comparative Example 1 continued to increase with the extension of the curing period, reaching 0.117% at 14 days, exceeding the 0.03% threshold. This indicates that ordinary refined slag powder only consumes part of the Ca(OH)2 through the pozzolanic reaction and cannot effectively block Na under the conditions of this experiment.+ K + The reaction between the active SiO2 and the active SiO2.

[0072] The expansion rates of the mortar rods in Example 1 at 3d, 7d, 10d, and 14d were 0.008%, 0.015%, 0.021%, and 0.026%, respectively, with a 14d expansion rate of less than 0.03%. Compared with Comparative Example 1, the 14d expansion rate of Example 1 decreased by 0.091 percentage points, indicating that the modified material composed of blast furnace slag and lithium slag can impart the final slag powder alkali-aggregate reaction inhibition ability.

[0073] Comparative Example 2

[0074] The difference between this comparative example and Example 1 is that the mass percentages of blast furnace slag and lithium slag in the modified material are 80% and 20%, respectively. The modified material still accounts for 30% of the total mass of the final slag powder, and the refining slag accounts for 70% of the total mass of the final slag powder.

[0075] Taking the preparation of 10,000 kg of slag powder as an example, 7,000 kg of refining slag, 2,400 kg of blast furnace slag, and 600 kg of lithium slag are weighed out. The lithium slag used has a Li2O mass content of 1.06%, therefore the Li2O mass content in the modified material is approximately 0.21%.

[0076] After all raw materials are batched, they are fed into a ball mill for simultaneous grinding to obtain the slag powder of this comparative proportion.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 1 is that the mass percentages of blast furnace slag and lithium slag in the modified material are 60% and 40%, respectively. The modified material still accounts for 30% of the total mass of the final slag powder, and the refined slag accounts for 70% of the total mass of the final slag powder.

[0079] Taking the preparation of 10,000 kg of slag powder as an example, 7,000 kg of refining slag, 1,800 kg of blast furnace slag, and 1,200 kg of lithium slag are weighed out. The Li2O mass content in the lithium slag used is 1.06%, therefore the Li2O mass content in the modified material is approximately 0.42%.

[0080] After all raw materials are batched, they are fed into a ball mill for simultaneous grinding to obtain the slag powder of this comparative proportion.

[0081] Experimental Example 2: Comparative Experiment with Different Amounts of Lithium Slag Added

[0082] The alkali-aggregate reaction inhibition performance of the slag powder obtained from Comparative Example 2, Example 1 and Comparative Example 3 was tested using the same rapid mortar bar method as in Experimental Example 1. The test results are shown in Table 7.

[0083] Table 7. Experimental results with different amounts of lithium slag.

[0084] The 14-day expansion rate of mortar bars under different lithium slag dosage conditions is as follows: Figure 2 As shown in Table 7, when the mass percentage of lithium slag in the modified material increased from 20% to 30%, the 14-day expansion rate decreased from 0.042% to 0.026%, meeting the requirement of less than 0.03% for effective inhibition. Further increasing the mass percentage of lithium slag to 40% reduced the 14-day expansion rate to 0.019%, but the SO3 content introduced by the lithium slag increased accordingly. Table 7 shows that in Comparative Example 2, when the mass percentage of lithium slag in the modified material was 20%, the 14-day expansion rate was 0.042%, exceeding the 0.03% threshold, indicating that insufficient lithium content cannot effectively inhibit alkali-aggregate reaction.

[0085] In Comparative Example 3, increasing the mass percentage of lithium slag in the modified material to 40% reduced the 14-day expansion rate to 0.019%, but the SO3 mass content in the lithium slag used in this embodiment reached 15.51%. Increasing the amount of lithium slag will simultaneously increase the SO3 content in the final slag powder, thereby increasing the risk of sulfate expansion. Example 1 uses a modified material composed of 30% lithium slag and 70% blast furnace slag, with a 14-day expansion rate of 0.026%, while simultaneously controlling the SO3 mass content in the final modified lithium slag powder to within 3.0%, thus achieving a balance between alkali-aggregate reaction inhibition, stability, and activity.

[0086] Comparative Example 3 illustrates that while increasing the amount of lithium slag can further reduce the 14-day expansion rate of the mortar bars, it also increases the amount of SO3 introduced. In Example 1, the mass percentage of lithium slag in the modified material was controlled at 30% to balance the alkali-aggregate reaction inhibition performance, cementitious activity, and SO3 content control.

[0087] Example 2

[0088] In this embodiment, the lithium slag modified slag powder obtained in Example 1 is used to prepare C30 concrete.

[0089] The total amount of cementitious materials used in C30 concrete is 280 kg / m³. 3 In Example 1, the lithium slag modified powder was used to replace PO 42.5 ordinary Portland cement at a rate of 25% of the total mass of cementitious materials. The cement content in the concrete was 210 kg / m³. 3 The dosage of lithium slag modified slag powder is 70 kg / m³. 3 The amount of medium sand used is 780 kg / m³ 3 The amount of crushed stone with a particle size of 5-25mm is 1020kg / m³. 3 The tap water consumption is 162 kg / m³ 3 The dosage of polycarboxylate superplasticizer is 3.05 kg / m². 3 .

[0090] Cement, lithium slag modified slag powder, medium sand and crushed stone are added to a concrete mixing equipment for mixing, and then tap water and polycarboxylate superplasticizer are added and mixed to obtain C30 concrete mixture.

[0091] Comparative Example 4

[0092] This comparative example uses pure cement to prepare C30 concrete without adding mineral admixtures. The amount of PO 42.5 ordinary Portland cement in the concrete is 280 kg / m³. 3 The amount of medium sand used is 780 kg / m³ 3 The amount of crushed stone with a particle size of 5-25mm is 1020kg / m³. 3 The tap water consumption is 165 kg / m³ 3 The dosage of polycarboxylate superplasticizer is 3.20 kg / m². 3 .

[0093] The concrete mix proportions for Example 2 and Comparative Example 4 are shown in Table 8.

[0094] Table 8. Mix Proportions for C30 Concrete

[0095] Test Example 3: Concrete Workability and Compressive Strength Test

[0096] Slump tests were performed on the concrete mixtures of Example 2 and Comparative Example 4. The slump of Comparative Example 4 was 130 mm, and the slump of Example 2 was 145 mm. Example 2 achieved a slump of 145 mm even with lower water and polycarboxylate superplasticizer dosages than Comparative Example 4, indicating that the C30 concrete incorporating lithium slag modified powder still possesses good flowability.

[0097] The concrete specimens prepared in Example 2 and Comparative Example 4 were subjected to standard curing, and their compressive strength at 7 days and 28 days was tested. The test results are shown in Table 9.

[0098] Table 9 Compressive Strength of C30 Concrete

[0099] The 7-day compressive strength of Example 2 was 21.1 MPa, lower than that of Comparative Example 4 (22.4 MPa), indicating that the hydration rate of blast furnace slag and lithium slag is lower than that of cement in the early stages. The 28-day compressive strength of Example 2 was 37.5 MPa, while that of Comparative Example 4 was 36.8 MPa. The 28-day compressive strength of Example 2 met the design strength requirements of C30 concrete, demonstrating that when lithium slag-modified powder is used to replace cement at an equal amount of 25% of the total mass of cementitious materials, it does not affect the concrete from reaching its design strength.

[0100] Experimental Example 4: Alkali-Aggregate Reaction Inhibition Test in Engineering Mix Proportions

[0101] The prepared mortar was prepared according to the cementitious material ratio of Example 2, and the alkali-aggregate reaction inhibition performance was tested using the rapid mortar bar method. The 14-day expansion rate of the prepared mortar of Example 2 was 0.027%, which is lower than the judgment limit of 0.03%.

[0102] The mortar prepared using the pure cement cementitious system in Comparative Example 4 had a 14-day expansion rate of 0.132%, exceeding the judgment limit of 0.03%. These results indicate that the lithium slag modified powder obtained in Example 1, when used to replace cement at 25% of the total mass of cementitious materials, can still effectively inhibit alkali-aggregate reaction in C30 concrete cementitious systems.

[0103] In summary, this invention, through the combination of refining slag, blast furnace slag, and lithium slag, enables blast furnace slag to participate in hydration and reduces the alkali-aggregate reaction conditions in the pore solution. Lithium slag provides lithium components to reduce the formation of expansive alkali-silica gel, and co-grinding improves the dispersion of each raw material. When the mass ratio of refining slag, blast furnace slag, and lithium slag is 70:21:9, the resulting lithium slag-modified slag powder can reduce the 14-day expansion rate of mortar bars that replace cement at a rate of 25% of the total cementitious material mass to below 0.03%, while maintaining stability and 28-day activity, and can be used in the preparation of C30 concrete, provided that the SO3 mass content does not exceed 3.0%.

[0104] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit of the present invention should fall within the protection scope defined by the present invention.

Claims

1. A lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete, characterized in that, include: The refining slag, blast furnace slag and lithium slag are provided, wherein the mass ratio of the refining slag, blast furnace slag and lithium slag is 70:21:9; The lithium slag contains Li2O. The blast furnace slag and lithium slag constitute the modified material, and the mass percentages of the blast furnace slag and lithium slag in the modified material are 70% and 30%, respectively. The refining slag, blast furnace slag and lithium slag are mixed and ground to form the modified lithium slag powder, and the SO3 mass content in the modified lithium slag powder does not exceed 3.0%.

2. The lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 1, characterized in that, The lithium slag contains 1.06% Li2O by mass, and the modified material contains 0.30% to 0.34% Li2O by mass.

3. The lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 1, characterized in that, The lithium slag comprises the following chemical composition by mass percentage: CaO 15.45%, SiO2 44.53%, Al2O3 19.48%, MgO 0.59%, Fe2O3 1.87%, SO3 15.51%, Na2O 0.52%, K2O 0.58%, and Li2O 1.06%.

4. The lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 1, characterized in that, The refining slag comprises the following chemical composition by mass percentage: CaO 43.26%, SiO2 26.18%, Al2O3 10.72%, MgO 8.54%, Fe2O3 6.31%, SO3 0.58%, Na2O 0.21%, and K2O 0.34%.

5. The lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 1, characterized in that, The 28-day activity index of the modified lithium slag powder is not less than 97%; when the modified lithium slag powder replaces cement by an equal amount of 25% of the total mass of cementitious materials, the 14-day expansion rate measured by the rapid mortar bar method is less than 0.03%.

6. A method for preparing lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete as described in any one of claims 1 to 5, characterized in that, include: Refining slag, blast furnace slag and lithium slag were obtained respectively, and the mass content of Li2O in the lithium slag and the mass content of SO3 in the refining slag, blast furnace slag and lithium slag were detected. The amount of lithium slag added is determined based on the mass content of Li2O in the lithium slag. Blast furnace slag and lithium slag are mixed at a mass ratio of 70:30 to prepare a modified material, so that the mass content of Li2O in the modified material is 0.30% to 0.34%. The refining slag and modified material are mixed at a mass ratio of 70:

30. The SO3 mass content after mixing is calculated based on the SO3 mass content in the refining slag, blast furnace slag and lithium slag, so that the calculated SO3 mass content does not exceed 3.0%. The refined slag, blast furnace slag and lithium slag after batching are mixed and simultaneously ground to obtain the modified lithium slag powder.

7. The method for preparing lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 6, characterized in that, When determining the amount of lithium slag to be added, the mass content of Li2O in the modified material is calculated according to the following formula: C = aC1 + bC2; In the formula, C is the mass content of Li2O in the modified material, a is the mass fraction of blast furnace slag in the modified material, C1 is the mass content of Li2O in the blast furnace slag, b is the mass fraction of lithium slag in the modified material, and C2 is the mass content of Li2O in the lithium slag.

8. The method for preparing lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 6, characterized in that, When the mass content of Li2O in different batches of lithium slag changes, the amount of lithium slag and blast furnace slag added is adjusted so that the mass content of Li2O in the modified material is between 0.30% and 0.34%, and the sum of the mass percentages of blast furnace slag and lithium slag is 100%.

9. The method for preparing lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 6, characterized in that, The simultaneous grinding process involves feeding the prepared refining slag, blast furnace slag, and lithium slag into a ball mill for grinding, so that the three raw materials are refined and uniformly mixed during the grinding process.

10. The method for preparing lithium slag modified slag powder for inhibiting alkali-aggregate reaction in concrete according to claim 6, characterized in that, After obtaining the modified lithium slag powder, the modified lithium slag powder is subjected to stability testing and activity index testing. The modified lithium slag powder with qualified boiling stability, 28-day activity index not less than 97% and SO3 mass content not exceeding 3.0% is determined as the finished product.